Ecological Optimization Strategies for Chang’an Sandy Polder in Hangzhou Based on the Evolution of Landscape Patterns and Ecosystem Services - Weicheng LI; Shixian SHEN (Fengjing Yuanlin)
ObjectiveThis research aims to analyze the evolution of landscape patterns and ecosystem services over two decades in Chang’an sandy polder, with a focus on understanding the relationship between landscape pattern and ecosystem services, particularly carbon storage and habitat quality. The goal is to provide insights into sustainable ecological design strategies that enhance landscape heterogeneity and connectivity, optimize agricultural productivity, and support regional ecological function.MethodsUsing high-resolution satellite data in 2000, 2009, and 2022, the research classifies land use into five categories: residential land, aquaculture pond, cultivated and garden land, woodland and grassland, and other land uses. The land-use maps for each period are manually drawn in ArcGIS Pro and converted into a grid format with a 1 m² resolution. Landscape pattern indices are calculated using Fragstats 4.2 software, incorporating indicators such as number of patches (NP), patch density (PD), percentage of landscape (PLAND), largest patch index (LPI), aggregation index (AI), contagion index (CONTAG), landscape shape index (LSI), and shannon diversity index (SHDI). Ecosystem services are quantified using the InVEST model, specifically for purpose of assessing carbon storage and habitat quality. Carbon pool parameters are adapted from previous research in combination with local conditions, considering above-ground biomass, below-ground biomass, soil organic carbon, and dead organic matter. Habitat quality is assessed by combining habitat suitability with the spatial influence of threat factors. A Pearson correlation analysis is conducted using SPSS 26 to assess the relationships between landscape pattern indices and ecosystem services at different time points. Based on the analysis results, different ecological design strategies are proposed, and their optimization effects are simulated and evaluated.ResultsOver the past 20 years, Chang’an sandy polder has undergone significant land-use changes, with aquaculture pond replacing cultivated and garden land as the dominant land-use type. This transition has led to increased landscape fragmentation, as indicated by higher patch density (PD) and lower aggregation index (AI). As a result, carbon storage has declined due to the reduction in cultivated and garden land, which store higher amounts of carbon compared to aquaculture ponds. However, habitat quality has improved, driven by the expansion of woodland and grassland and the ecological benefits of aquaculture ponds. In Chang’an sandy polder ecosystem, changes in landscape patterns significantly impact carbon storage and habitat quality. Carbon storage tends to be higher in less fragmented and more aggregated landscapes, whereas habitat quality benefits from increased shape complexity. These findings suggest that in the planning process, habitat quality can be improved by adjusting landscape structure while balancing carbon storage function. Based on the results, three key ecological design strategies are proposed: 1) Enhancement of landscape heterogeneity and complexity: By increasing land-use diversity and restoring the Fengtian system (floating garden), the landscape can become more resilient and productive, balancing agricultural production with biodiversity conservation. 2) Optimization of patch and corridor configurations: By connecting fragmented patches and improving landscape connectivity, ecological corridors can support species movement and enhance habitat quality. This strategy also emphasizes creating visually appealing landscapes that enrich human experience. 3) Development of integrated dike – pond (Jitang) agricultural systems: The traditional “mulberry – dike fishpond” and “fruit – dike fishpond” systems can be revitalized to create sustainable, closed-loop farming practices. These systems enhance nutrient cycling, reduce pollution, and improve ecosystem services such as carbon storage and water purification. By simulating the changes in landscape pattern and ecosystem services after applying these strategies, it is found that both landscape pattern and ecosystem services are improved.ConclusionThis research demonstrates the complex interplay between landscape patterns and ecosystem services in Chang’an sandy polder. The results highlight the need for integrated ecological design strategies that enhance both landscape complexity and ecosystem service provision. In conclusion, this research provides valuable insights for the conservation and ecological design of polder systems in island environments. The proposed ecological design strategies offer a framework for optimizing landscape patterns while supporting the ecological function of traditional agricultural systems. The innovation of this research is to embed the pattern – process analysis method in landscape ecology into traditional agricultural landscape design, and attempt to construct a closed-loop research framework covering the whole process of analysis – diagnosis – design – verification, thus providing empirical cases and methodological support for the ecological design of small and medium-scale polder areas. Future research could incorporate more refined spatiotemporal dynamic models, and integrate remote sensing monitoring with socio-economic data to systematically analyze the coupled relationships among human activities, policy changes, landscape patterns, and ecosystem services. This approach would enhance the applicability of the research and its value in supporting decision-making.